Competing for narrative authority in capital markets: Activist short sellers vs. financial analysts. (July 2022) - Stolowy, Hervé; Paugam, Luc; Gendron, Yves
Abstract: Activist short sellers (AShSs) and financial analysts are information intermediaries who analyze firm disclosures as well as produce and disseminate influential investment narratives. This study aims to better understand narrative challenges surrounding the legitimate expertise of financial analysts. Specifically, we examine how AShSs challenge sell-side financial analysts' narrative authority (i.e., the perception that they produce expert knowledge) in interpreting firms' performance and future prospects. We investigate how analysts respond (or do not respond) to this challenge. We use 442 AShS reports, 12 interviews with AShSs and analysts, and analysts' stock recommendations and target prices. In their criticisms of analysts (found in one-third of reports), AShSs frequently frame analysts as lacking market expertise and critical thinking – two core dimensions of analysts' narrative authority. Sixty-six percent of analysts, although explicitly criticized in AShS reports, do not engage in written responses in their equity research reports because they reportedly either adopt a renunciation attitude to the challenge or they engage in off-the-record discussions with certain market participants. However, 34% of analysts respond overtly by counter-framing AShSs as lacking market expertise and objectivity. After the dissemination of AShS reports, analysts, on average, do not revise their highly visible stock recommendations but they revise target prices downward. Theoretically, this study extends our understanding of the construction of narrative authority in capital markets as we examine a challenge to the expertise of influential information intermediaries.